Fresno County Courthouse Park: Courthouse, Statues and Sculptures - Watkins, Howard::::::::: (1989)
Clement Renzi's "Forum for Better Understanding" sculpture located at M and Mariposa Streets Sculpture now located at Fresno County Plaza lower level (M and Tulare)